Relationship between foreign macroeconomic conditions and Asian-Pacific public real estate markets: The relative influence of the US and China - Kim Hiang Liow; Yuting Huang; Kai Li Heng (International Journal of Financial Studies, 2019)
The aim of this paper was to examine the relationship between changes in the US and China macroeconomic conditions and the excess returns of nine Asian-Pacific public real estate markets (Singapore, Indonesia, Malaysia, the Philippines, Thailand, Australia, Taiwan, Hong Kong, and Japan). We found that there are insignificant correlations between macroeconomic conditions in the US and China and the real estate markets' excess returns. Additionally, whilst the US macroeconomic factors show stronger causal relationships with the real estate markets in the long run, China's macroeconomic variables have experienced a stronger causal relationship in the short run. Finally, key macroeconomic variables, such as the industrial production output index, long-term interest rates, and economic policy uncertainty, produced fluctuating impulse responses to shocks from the US and China. Overall, we conclude that the US economy continues to have a dominant influence in the Asian-Pacific real estate markets. However, during economic crises and in the short run, the impact of China's economy grows significantly and outweighs that of the US In the context that a high degree of economic and financial integration has affected the interdependent level of international financial markets, the Asian-Pacific securitized real estate markets' performances are also impacted by global shocks.
Keywords: 330; Asia-Pacific public real estate markets; economic policy uncertainty; generalized impulse response functions; macroeconomic variables; non-linear causality tests